The trade effects of the information provision about forced and child labor - Margaryta Klymak (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2020)
Does the provision of information regarding what foreign goods might be produced with child and forced labor affect imports to the U.S.? I investigate this question using the largest naming and shaming strategy ever implemented worldwide: inclusion on the U.S. government's list of goods produced with child or forced labor. This paper shows empirically that information provision decreased United States imports of goods believed to be made using child and forced labor. The results are mainly driven by the goods closer to the point of consumption, where consumers might reasonably be expected to penalise goods which rely on such labor, while no effect has been found for intermediate goods. This implies that public information strategies may be efficient in disincentivising the reliance on child and forced labor in the case of export of certain goods but not others.
Keywords: F14; J81; O11; 330; international trade; child labor; forced labor; social labelling